Шляхи презентації предметної інформації при навчанні галузевого перекладу - Купрієнко, Юлія Вікторівна (Житомирський державний університет ім. Івана Франка, 2017)
Статтю присвячено важливості формування предметного й термінологічного компонентів фахової компетентності перекладача професійно-орієнтованих текстів. З цією метою було складено поняттєві схеми на основі англомовних текстів за темою "Мова комп’ютерного програмування", які були детально проаналізовані. Були зроблені висновки про необхідність розробки експериментальної методики навчання галузевого перекладу на основі вищезгаданих схем.

The article is devoted to the profession-oriented text analysis for the field of computer science (topic – Computer Programming Language). It describes the process of drawing up a notional scheme and the selection of English and Ukrainian terminological units for the acquisition of TC subject-matter and terminological components. The following steps were taken to solve the abovementioned task: 1) The original English texts (topics – Business and education oriented languages, Object-oriented languages and Declarative languages) were chosen to translate and analyze; 2) The texts were translated into Ukrainian; 3) The appropriate terms were selected in both English and Ukrainian texts; 4) English-Ukrainian and Ukrainian-English terminological vocabularies were made based on the selected terms; 5) The main subject-matter notions of both English and Ukrainian texts were selected and their hierarchy was established; 6) The notional schemes based on the abovementioned notions and their hierarchy were made. The notional schemes represent subject-matter knowledge that can help to form professional translator's competence. The methodology of using such schemes while non-fiction translator teaching needs to be studied within the framework of our further research.
Presentation methods of subject-matter information while non-fiction translator teaching
Keywords: предметна компетентність; термінологічна компетентність; поняттєва схема; комп'ютерні науки; мова комп'ютерного програмування; computer programming language; subject-matter competence; terminological competence; notional scheme; computer sciences